2021
DOI: 10.1016/j.heliyon.2021.e06110
|View full text |Cite
|
Sign up to set email alerts
|

Land tenure and property rights, and household food security among rice farmers in Northern Nigeria

Abstract: There are growing campaigns to promote land titling to secure Land Tenure and Property Rights (LTPRs) in African agriculture. Theoretically, deed registration should reduce land disputes, facilitate land use as collateral for loans, and stimulate investment in land improvement for increased productivity, income and food security. Empirical evidence in these regards, however, remains anecdotal, and sometimes conflicting. This paper reports a study that examined LTPRs' among smallholder rice farmers in Northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
(42 reference statements)
4
3
0
Order By: Relevance
“…The holder of such title exercises full management rights over his/her holdings. The finding is in line with [26] that concluded that inheritance is the principal mode of land acquisition in Northern part of Nigeria. However, the finding differs with [27] who reported that purchase was the major means of acquiring land in South Eastern Nigeria.…”
Section: Mode Of Land Acquisitions By Rice Farmerssupporting
confidence: 91%
“…The holder of such title exercises full management rights over his/her holdings. The finding is in line with [26] that concluded that inheritance is the principal mode of land acquisition in Northern part of Nigeria. However, the finding differs with [27] who reported that purchase was the major means of acquiring land in South Eastern Nigeria.…”
Section: Mode Of Land Acquisitions By Rice Farmerssupporting
confidence: 91%
“…Additionally, the high costs of obtaining land titles would limit title registration to lands situated in most urban and peri-urban areas, increasing household food insecurity. Our finding is supported mainly by Kehinde et al (2021) for Nigeria. The household size variable's negative and statistically significant coefficients suggest that households with more members are negatively associated with food insecurity.…”
Section: Resultssupporting
confidence: 73%
“…According to the findings, 43 percent of the smallholders sampled had sufficient HDDS, while 39 percent had a moderate level [ 93 ]. As proven by Kehinde et al [ 94 ], there is a link between HDDS, and tenure security expressed in purchasing land and the prevalence of customary land rights.…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuating patterns of rainfall and the impact of climate change on agriculture can have several adverse effects, including reduced crop yields and compromised nutritional quality [ 103 ]. Apart from the fluctuating rainfall, lack of knowledge on coping and adaptation strategies is seen as one of the causes of food insecurity in the study area because most of the farmers depend on rain for their agricultural activities [ 94 ].…”
Section: Discussionmentioning
confidence: 99%